Dairy development in Kenya: the past, the present and the future - Thorpe, W.R.; Muriuki, H.G.; Omore, Amos O.; Owango, M.O.; Staal, Steven J. (International Livestock Research Institute, 2000)
Large increases in demand for milk and dairy products in developing countries are projected for the next 25 years. These represent exciting market opportunities for smallholders, such as those in Kenya, which has over 85% of the dairy cattle population in eastern Africa. Currently Kenya’s per capita availability of milk is four to seven times higher than the other countries in the region. The widespread adoption of dairy cattle by smallholders in Kenya was stimulated by several interacting factors: smallholder communities who kept cattle and who had milk as an important part of their diet; a sub-tropical geography suitable for dairy cattle; the presence of significant dairy populations (owned by settler farmers); and the conducive policy and institutional environments provided by successive Governments.